P49 Treating hepatitis C in the patient's home: a hospital and homecare partnership. (6th September 2011) - Jack, K; Barnett, J; Thomson, B
Abstract : Introduction: It is long established that the UK has poorer outcomes regarding numbers of patients treated with antivirals for chronic hepatitis C (HCV) than it's European counterparts. Exploring alternative models of care that will facilitate the engagement of those whom regular hospital attendance would be a barrier to treatment is important if one is to reduce the incidence of end stage liver disease among this group of patients. Against this backdrop we initiated a project in Nottingham to deliver care in tandem with a community nursing service. Aim: To treat HCV infected patients with pegylated interferon and ribavirin in the patient's home via a partnership between secondary care and an established homecare company. Method: Patients with stable HCV infection and no evidence of decompensated liver disease are offered this model of care in the hepatitis clinic and referred to the homecare company by the Consultant or Specialist Nurse. The antiviral drugs are delivered directly to the patient's home, and a skilled homecare nurse trained in the management of HCV visits the patient to undertake: teaching how to self inject pegylated interferon and take ribavirin correctly; draw blood samples for monitoring treatment progress and safety, to assess side effects and provide nursing care in managing these; and regularly report back to the referring clinician. Nursing support is available to patients 24 h a day. Once treatment is complete the patient returns to the hepatitis clinic to be reviewed. Results: Since this model's inception in February 2004, approximately 110 patients were offered the option of homecare. 87 patients elected to be treated at home and were referred by the secondary care HCV clinic using an agreed proforma. Investigations during treatment were conducted using the same schedule as the specialist clinic and hospital staff reviewed the results. The specialist team took all decisions on changes to drug treatment. Treatment outcomes and drop out rates are comparable to hospital-managed clinics, but the non-attendance rates are exceptionally low; only two home visits have been missed by patients. No adverse events as a result of receiving treatment and monitoring at home have occurred. Furthermore this model of care is cost effective; drugs are supplied VAT-free by not being routed into the hospital pharmacy, and this offsets the home nursing cost. Conclusion: Our results demonstrate that homecare treatment for HCV infection is feasible, safe and the preferred option of most patients. It is well tolerated by patients with very high compliance rates which we anticipate will lead to improvements in treatment outcomes. We suggest that this innovative homecare model can be an important facet of hospital HCV services, and thus be a major means of facilitating the engagement of more patients into therapy without an additional burden of nursing staff costs.